ANALISIS PENGENDALIAN KUALITAS PRODUK BIJI PLASTIK UD. LESTARI - Laila, Nurotul Sofi Anisyaful (Manajemen Bisnis, 2018)
The aim of this study was to examine the problems and solutions to quality control of pellets at UD Lestari. The data were collected by using observation, documentation, and interview. Then, the data were analyzed by using cause-effect and pareto diagrams. Cause-effect diagram used to found the caused of damage and eliminate it and pareto diagram used to determine and to sort the total of damage from the largest to smallest. The results of the study showed that there were three kinds of problems, such as: different type of pellets, attached pellets to one another, and pellets chunk due to labor, raw material, machine, and method factors. The pareto diagram shows that the shaped plastic seed was a product damage most widely. The most dominant problem faced by UD Lestari was chunk pellets. Thus, the company should monitor labor, raw material, machine, and method used in processing the pellets.